KEYSER, D.J.P. Inventory of documents - KEYSER, D.J.P. (ARCA, 2018)
Minute book NP - transferred to PV 21, NP OFS collection, files II 18 and II 34
COVERAGE: 1942-1965
Keywords: KEYSER, D.J.P.; Inventories; Politicians; National Party